1997
DOI: 10.1038/385634a0
|View full text |Cite
|
Sign up to set email alerts
|

Decreased prefrontal dopamine D1 receptors in schizophrenia revealed by PET

Abstract: Schizophrenia is believed to involve altered activation of dopamine receptors, and support for this hypothesis comes from the antipsychotic effect of antagonists of the dopamine D2 receptor (D2R). D2R is expressed most highly in the striatum, but most of the recent positron emission tomography (PET) studies have failed to show any change in D2R densities in the striatum of schizophrenics, raising the possibility that other receptors may also be involved. In particular, the dopamine D1 receptor (D1R), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
341
3
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 654 publications
(363 citation statements)
references
References 23 publications
12
341
3
7
Order By: Relevance
“…Finally, a recent study reported decreases in dopamine D1 receptor mRNA in the frontal cortex of rats repeatedly treated with MK-801 (Healy and Meador-Woodruff 1996). These findings directly correspond with in vivo imaging studies of dopamine receptors that have revealed decreased prefrontal cortical dopamine D1 receptors in the schizophrenic brain (Okubo et al 1997).…”
Section: Validity Of the Subchronic Pcp-based Animal Model Of Schizopsupporting
confidence: 77%
“…Finally, a recent study reported decreases in dopamine D1 receptor mRNA in the frontal cortex of rats repeatedly treated with MK-801 (Healy and Meador-Woodruff 1996). These findings directly correspond with in vivo imaging studies of dopamine receptors that have revealed decreased prefrontal cortical dopamine D1 receptors in the schizophrenic brain (Okubo et al 1997).…”
Section: Validity Of the Subchronic Pcp-based Animal Model Of Schizopsupporting
confidence: 77%
“…Second, hypofrontality in schizophrenia is alleviated by systemic administration of indirect or direct dopaminergic agonists, such as amphetamine (Daniel et al 1991) or apomorphine (Daniel et al 1989;Dolan et al 1995). Finally, a recent positron emission tomographic (PET) study has suggested that the dopamine D 1 -receptor may be downregulated in schizophrenia (Okubo et al 1997). Thus, it seems that one component of the cognitive dysfunction of schizophrenia is associated with reduced frontal dopaminergic transmission.…”
Section: Neurochemistry Cortical Dopamine Dysfunctionmentioning
confidence: 99%
“…First, many clinically efficacious antipsychotics are potent dopamine receptor antagonists (Seeman 1992). Second, dopamine receptors (Okubo et al 1997) or the release dynamics of dopamine terminals (Wong et al 1997) are markedly altered in living schizophrenic brains. Third, several psychoactive substances (e.g., amphetamine, phencyclidine) abnormally augment dopamine transmission and induce psychotic symptoms indistinguishable from schizophrenia.…”
mentioning
confidence: 99%